Meningkatkan Kemampuan Mengenal Huruf Konsonan Melalui Media Buku Belajar ABC Berbasis Augmented Reality (AR) Bagi Anak Disabilitas Intelektual Ringan Fase B Kelas III di SLB Negeri 1 Solok - Wahyu, Sri Mulia; Zulmiyetri, Zulmiyetri; Mahdi, Arisul (Universitas Negeri Padang, 2025)
The background of this study stems from problems identified at SLB Negeri 1 Solok, namely that students with mild intellectual disabilities still have difficulty recognising consonants comprehensively. This study aims to strive for improvement ability to recognise consonant letters through an ABC learning book based on augmented reality (AR). This study employed an experimental method using a SingleSubject Research (SSR) design model A-B. The techniques employed for data collection include involve tests, and the data are analysed visually in the form of graphs. The research subjects were third-grade students in phase B with mild intellectual disabilities. The findings indicated that during the baseline phase, a stable score of 17 was obtained, while at the intervention condition, the score increased steadily to 67. This indicates a positive impact from the use of AR media. However, the effectiveness of the media cannot yet be conclusively determined due to the short intervention period, which has not demonstrated the sustainability of results in the long term.